Kif21B mediates the effect of estradiol on the morphological plasticity of mouse hippocampal neurons - Ganchala, Danny; Pinto-Benito, Daniel; Baides, Elisa; Ruiz-Palmero, Isabel; Grassi, Daniela; Arevalo, Maria Angeles (Frontiers in Molecular Neuroscience, 2023)
Neurons are polarized cells, and their ability to change their morphology has a functional implication in the development and plasticity of the nervous system in order to establish new connections. The neuronal shape and connectivity are strongly influenced by extracellular factors. For instance, the developmental actions of estradiol on hippocampal neurons are well characterized, and we showed that Ngn3 mediates these actions. In the present study, we assessed the involvement of kinesin Kif21B in the estradiol-dependent signaling mechanisms to regulate neuritogenesis in primary mouse hippocampal neurons. It has been showed that Kif21B regulates microtubule dynamics and carries out retrograde transport of the TrkB/BDNF complex, being essential for neuronal development. Here we show that estradiol treatment induces an increase in BDNF expression, and estradiol and BDNF modify neuron morphology through TrkB signaling. Treatment with K252a, a TrkB inhibitor, decreases dendrite branching with no effect on axonal length, whereas, when applied in combination with estradiol or BDNF, it blocks their effects on axons but not on dendrites. Notably, the downregulation of Kif21B abolishes the actions of estradiol and BDNF in both the axon and dendrites, suggesting that Kif21B is required for the effects of estradiol and BDNF on neuronal morphology, but phosphorylation-mediated activation of TrkB is essential only for axonal growth. In addition, Kif21B silencing also decreases Ngn3 expression, and downregulation of Ngn3 blocks the effect of BDNF on neuron morphology. Taken together, we report that the Estradiol/BDNF/TrkB/Kif21B/Ngn3 is a new and essential pathway mediating hippocampal neuron development.